Legal Analysis of The Ideal Age of Marriage in Maintaining Marriage Is Reviewed from The Opinions of Psychologists and Scholars - Fuad Hariri; Zainal Arifin Purba (Journal Equity of Law and Governance, 2024)
This study examines the ideal marriage age in relation to maintaining marriage by examining the opinions of academics and psychologists. This research explores the limitations of the ideal marriage age, determinants of divorce at that age, and how the marriage age has been affected by the birth of Law No. 16 of 2019 and the opinions of psychologists and academics. It employs a qualitative technique with a case study approach. There are still a lot of divorces, according to the results, even if the legal marriage age is now 19 years old. The high divorce rate is due in part to people not being emotionally and financially prepared for marriage or not realizing its ultimate purpose. A spouse's emotional and spiritual maturity, rather than their chronological age, is the most important factor in a healthy marriage, according to psychologists and academics. As a means of prevention, they also advise having a comprehensive pre-nikah bimbingan and mental health education. The research indicates that society is not the only factor contributing to the success of marriage, including mental, spiritual, and understanding aspects that are related to marriage goals that are crucial.